Pelatihan Aplikasi Microsoft Mathematics Bagi Siswa SMA Muhammadiyah Boarding School Kota Bengkulu - Maryaningsih Maryaningsih; Dian Mardiati Sari; Nofi Qurniati; M.Adhlan Alhawari; Bagas Fauzan (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Microsoft Mathematics application is an application that can be used by students to learn Mathematics. This application not only provides answers but provides an explanation of the stages in solving math problems. Most of the XII grade students of SMA Muhammadiyah Boarding School still have difficulties in learning Mathematics, and do not know and understand the use of Microsoft Mathematics applications. Based on this, training is held for students with the aim that students are skilled in using the application that improve students' abilities in solving math problems. The result of the evaluation for this activity is that students can use the application to solve math problems properly and correctly.